Knowledge and Attitudes of Pregnant Women Regarding Triple Elimination Screening in Buleleng Regency, Bali, Indonesia - Sulyastini, Ni Komang; Sekarini, Ni Nyoman Ayu Desy; Wilandari, Made Ririn Sri; Pratiwi, Putu Irma (Bali Medical and Wellness Journal, 2025)
Background: Triple elimination screening (for HIV, syphilis, and hepatitis) is a routine part of antenatal care, aimed at preventing transmission from mother to child. Objectives: This study investigated the relationship between pregnant women's knowledge and attitudes and their participation in triple elimination screening in Buleleng Regency, Bali. Methods: A cross-sectional, quantitative study was conducted with 371 pregnant women recruited from 36 midwife practices using cluster random sampling. Data on knowledge, attitudes, and screening participation were collected using a questionnaire. Chi-square tests were used to analyze the data. Results: Most participants were between 20 and 35 years old (84.6%), had a secondary education (60.1%), were multigravida (73.9%), and were in their third trimester (46.4%). Chi-square tests showed no significant relationship between knowledge and participation in screening for HIV (p = 0.25), syphilis (p = 0.10), or hepatitis (p = 0.06). However, a significant association was found between positive attitudes and screening participation for HIV (p = 0.04), syphilis (p = 0.05), and hepatitis (p = 0.04). Specifically, over 97% of women with positive attitudes underwent screening for HIV, syphilis and hepatitis. Conclusion: Positive attitudes are significantly associated with increased participation in triple elimination screening among pregnant women. Continued education from healthcare providers is important to improve screening rates.